Trade Openness and Growth: A Network-Based Approach - Georg Duernecker; Moritz Meyer; Fernando Vega-Redondo (Center for Economic Studies and ifo Institute (CESifo), 2021)
In this paper, we propose a novel approach to the study of international trade that leads to a measure of country openness that is quite different from the various alternatives proposed by the received literature. In contrast to these, our measure does not use indicators of aggregate trade intensity, trade policy, or trade restrictiveness but relies on a broad systemic viewpoint on the effects of trade. More specifically, it goes beyond direct trade connections and measures a country's level of integration in the world economy through the full architecture of its second, third, and all other higher-order connections in the world trade network. We apply our methodology to a sample of 204 countries spanning the period from 1962 to 2016 and perform a Bayesian analysis of model selection to identify the most important correlates of growth. The analysis finds that there is a sizable and significant positive relationship between our integration measure and a country's rate of growth, while that of the aforementioned traditional measures of outward orientation is only minor and statistically insignificant. We perform several sensitivity checks and conclude that our baseline findings are very robust to either different data sets or alternative variations of the integration measure. Overall, this suggests that a network-based approach to measuring country openness may provide a valuable perspective on economic growth.
Keywords: 330; globalization; trade integration; economic growth; network analysis; dynamic panel model; Bayesian model averaging